Cardio-Ankle Vascular Index as a Marker of Arterial Stiffness: Principles, Application, and Clinical Utility - Tavolinejad, Hamed; Pourmussa, Bianca; Chirinos, Julio A. (Current Hypertension Reviews, 2025)
Large artery stiffness (LAS) is widely recognized as a highly clinically relevant determinant of cardiovascular health and an independent prognostic marker. However, routine assessment of LAS has not yet been integrated into clinical practice. Arterial wall stiffness is dependent on distending pressure (i.e., mean arterial pressure), which may confound the interpretation of individual measurements. The cardio-ankle vascular index (CAVI) is an index of arterial stiffness designed to mitigate the dependence of pulse wave velocity on blood pressure. However, because CAVI incorporates pulse wave velocity measured between the heart and the ankle, it is influenced by both the stiffness of the aorta and medium-sized muscular arteries. Several observational, longitudinal studies have demonstrated that higher CAVI is associated with cardiovascular events and mortality, although most available data are derived from Asian populations. Future studies of CAVI are needed to establish its prognostic value in addition to traditionally used cardiovascular risk factors in the setting of primary prevention. This review aims to provide a brief overview of the definition, theoretical principles, practical considerations, key strengths and limitations, and the clinical utility of CAVI.
Keywords: cardiovascular disease